Pitting corrosion behaviour of aluminium alloys - Leon, Mei Chen (2013)
The present work is aimed to investigate the effect of temperature and concentration of solution on the pitting corrosion of AA6061 – T6 aluminium alloy and study its electrochemical behaviour and physical behaviour in sodium chloride (NaCl) solution using the polarization technique. The experiments were carried out under static conditions at different NaCl concentration solutions (3.5, 4.5 and 5.5) wt% and different temperatures (25, 35, 45, 55 and 65) oC. This experiment started with different NaCl concentration solutions at room temperature condition by using potentiostat/galvometer instrument. Water bath machine had been used to control the solution temperature in this experiment. Natural pitting corrosion experiment had been tested for 2 months in different NaCl concentration solutions. Comparison between two methods which were tested in different concentration was discussed. It was found experimentally that increasing in NaCl concentration and temperatures lead to decrease in the breakdown potential (E corr) and increase in corrosion rate of as-received materials. Based on the results obtained, the corrosion rate increased from 0.1529 mmpy to 0.3650 mmpy for the electrochemical experiment and 0.2517 mmpy to 0.4692 mmpy for natural pitting when concentration of the solutions increased from 3.5 wt% to 5.5 wt%. The influence of solutions’ temperature (25 – 65) oC on the pitting corrosion of AA6061-T6, showed the changes of the corrosion rate from 0.1529 mmpy to 1.205mmpy. In conclusion, the highest corrosion rate obtained at the highest solution temperature. The increased in concentration and temperature lead to the increasing of corrosion rate of AA6061-T6.